Letters from Iwo Jima - Yamashita, Iris; Cox, Joel; Roach, Gary D.; Watanabe, Ken 1959-; Ninomiya, Kazunari; Ihara, Tsuyoshi; Kase, Ryo; Nakamura, Shido; Kuribayashi, Tadamichi 1890 or 1-1945 (Clint Eastwood collection)
Sixty-one years ago, the United States and Japanese armies met on Iwo Jima. Decades later, hundreds of letters are unearthed from that stark island's soil. The letters give faces and voices to the men who fought there, as well as the extraordinary general who led them. Leading the defense is Lt. General Tadamichi Kuribayashi. With little defense other than sheer will and the volcanic rock of the island itself, Gen. Kuribayashi's unprecedented tactics transform what was predicted to be a quick and bloody defeat into nearly 40 days of heroic and resourceful combat